Sylwester Bębas, Mariusz Z. Jędrzejko, Kaja Kasprzak, Adam Szwedzik, Agnieszka Taper (red.), Cyfrowe dzieci. Zjawisko, uwarunkowania, kluczowe problemy, Wydawnictwo Aspra, Warszawa – Milanówek 2017, ss. 396 - Górka, Marek (Studia Edukacyjne, 2017)
.